The role of business information system in preventing small and medium enterprise from falling into the valley of death - Mootien, D.; Lallmahomed, M. Z. I. (FMLIC - Conference Proceedings, 2024)
Small and Medium Enterprises (SMEs) play a pivotal role in the Mauritian economy with their survival of paramount importance. However, those businesses faced challenges in the decision-making process such as not having the right data, wrong interpretation of data or a lack of knowledge. In addition to the recent increase in freight costs, business owners have been significantly impacted, resulting in higher prices for goods. Many systems have been developed to aid in the decision-making process. As technology evolves, the integration of Artificial Intelligence (AI) into these systems has materialised, leading to the emergence of Intelligent Decision Support Systems (IDSS) through the association of AI with Decision Support System (DSS). Given the dearth of research on IDSS in the Mauritian context, this study investigated the adoption of IDSS amongst SMEs in Mauritius. An extended framework comprising the technology, organisation, environment/technology acceptance model was employed. Using a purposive sampling technique, a crosssectional survey was carried out amongst 100 SMEs in order to gain insight into SMEs’ owners adoption of IDSS in their businesses. Salient findings from the hypothesis test showed that innovativeness is significantly related to both perceived usefulness and ease of use. Competitive advantage is shown to lead to perceived usefulness of IDSS and government support contributed to the perceived ease of use of IDSS. Given that respondents will mostly likely adopt IDSS if they perceive its innovative capability to their businesses. Proper awareness campaigns should be carried out to showcase the benefits and innovative features of IDSS. Moreover, Government support plays a crucial role in the adoption of SMES. The Government should provide incentives and further training to the SMEs on the IDSS. Overall, SMEs are interested in adopting a disruptive tool like IDSS and recognise IDSS as advantageous to their businesses, if necessary, support is available.
Keywords: Small and medium enterprise; Decision making; Intelligent decision support system; Mauritius